(untitled) (Research, Society and Development, 2024)
Objective: To review the literature on mini-implant-assisted rapid maxillary expansion (MARPE) for correction of transverse maxillary deficiency in adults. Methodology: Clinical, laboratory and literature review articles that addressed the topic in question were included. The research used articles in Portuguese and English. To prepare the review, a search was performed in scientific databases, such as SciELO, PubMed and Google Scholar. Literature review: MARPE is an orthodontic technique aimed at correcting maxillary atresia, especially in adult patients; unlike conventional RME, the incorporation of mini-implants in the palate ensures the expansion of the underlying basal bone, minimizing dentoalveolar inclination and expansion. Conclusion: It is a promising alternative for rapid expansion of the midpalatal suture, especially in young adults, when other conventional rapid maxillary expansion techniques fail. It stands out for being less invasive than surgical palatal expansion surgery.